Mobilitas Penduduk, Kemiskinan, dan Ketahanan Pangan di Daerah Bencana: Kasus Desa Timbulsloko, Kecamatan Sayung, Kabupaten Demak, Provinsi Jawa Tengah - Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2019)
The purpose of this study is to explain the relationship between migration, poverty,and fulfillment of food demand. Research design is a mixed method, combining survey and qualitative methods. The survey was conducted involving 100 samples of randomly selected households. While the qualitative method is carried out by in-depth interviews with selected households and key informants. The results of this study indicate that the impact of tidal flooding on the community economy is very significant. For example, more than one fifth of households fall into the poor category (per capita expenditure below the poverty line). One of the reasons is that tidal flooding has resulted in the loss of most people's livelihoods from agriculture. In addition, the loss of agricultural land has also resulted in the loss of food resources. In the end, this caused most households to rely on non-agricultural work, namely as laborers, outside the village. As a consequence they have to carry out non-permanent mobility as a way to overcome the economic problems they face. The interesting thing is they don't want to migrate to other places. One reason why they do not migrate is their inability to overcome economic barriers in the form of costs to migrate.